2009
DOI: 10.1186/1471-2261-9-13
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord stimulation in the treatment of refractory angina: systematic review and meta-analysis of randomised controlled trials

Abstract: Background: The aim of this paper was undertake a systematic review and meta-analysis of the use of spinal cord stimulation (SCS) in the management of refractory angina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 30 publications
2
85
0
4
Order By: Relevance
“…With appropriately selected patients at centers with interdisciplinary expertise, the trial-to-implant conversion rates can be quite encouraging: in the 65%-80% range for various diagnoses, 15 although from a nationwide perspective, the actual conversion rate remains less encouraging at approximately 41%. 7 The utility of this technology has been demonstrated in prospective randomized and observational studies, and in systematic literature reviews for various pathologies, including PPNP after structurally corrective lumbar spinal surgery, 6 complex regional pain syndrome, 27 chronic inoperable limb ischemia, 31 treatment-refractory angina, 28 and painful diabetic neuropathy. 3 Despite its proven efficacy for the PPNP population, there have been a few small studies that reported on the risk experienced by patients undergoing such intervention specifically in the context of managing neuropathic pain after lumbar spinal surgery, and whether those rates of complication are variable by surgical technique.…”
mentioning
confidence: 99%
“…With appropriately selected patients at centers with interdisciplinary expertise, the trial-to-implant conversion rates can be quite encouraging: in the 65%-80% range for various diagnoses, 15 although from a nationwide perspective, the actual conversion rate remains less encouraging at approximately 41%. 7 The utility of this technology has been demonstrated in prospective randomized and observational studies, and in systematic literature reviews for various pathologies, including PPNP after structurally corrective lumbar spinal surgery, 6 complex regional pain syndrome, 27 chronic inoperable limb ischemia, 31 treatment-refractory angina, 28 and painful diabetic neuropathy. 3 Despite its proven efficacy for the PPNP population, there have been a few small studies that reported on the risk experienced by patients undergoing such intervention specifically in the context of managing neuropathic pain after lumbar spinal surgery, and whether those rates of complication are variable by surgical technique.…”
mentioning
confidence: 99%
“…The authors did not demonstrate any difference in terms of exercise tolerance or overall quality of life between the groups. A meta-analysis of published studies has reported reduced angina attacks in SCS patients from 5.5 to 2.2 within 48 hours 35 . The ongoing multicenter RASCAL study aims to compare the efficacy and cost-effectiveness of SCS versus standard care in patients with the refractory angina 46 .…”
Section: Results Of Randomized Controlled Trialsmentioning
confidence: 99%
“…They must be a part of multidisciplinary treatment plan involving effective pharmacotherapy, physiotherapy, cognitive-behavioral therapy and pain interventions. There is a clear evidence supporting the use of spinal cord stimulation in patients with chronic pain of cardiac origin including refractory angina 35,80,83 . Treatment modalities involving the interruption of upper thoracic sympathetic chain or subcutaneous target field stimulation are promising but need further confirmation in the setting of a randomized controlled trial (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations